Effect of preparations with the viable yeasts Saccharomyces cerevisiae and LEVICA-25 on methanogens and in vitro ruminal methanogenesis - Galindo, Juana; Marrero, Yoandra; Gonz?lez, Niurca; Sosa, Areadne; Miranda, Ana L.; Aldana, Ana Irma; Moreira, Onidia; Bocourt, Ram?n; Delgado, Denia; Torres, Verena; Sarduy, Luc?a; Noda, Aida (Cuban Journal of Agricultural Science, 2010)
The objective of this work was to evaluate the effect of preparations with Saccharomyces cerevisiae yeasts and LEVICA-25 viable, in methanogens and in vitro ruminal methanogenesis. The experiment was conducted through the submerged culture technique. A completely randomized design was used. The treatments were: A) control, B) Saccharomyces cerevisiae, and C) LEVICA-25. The samplings were performed before incubation (hour 0), and at 4, 8, 12, and 24 h after the fermentation. Star grass (Cynodon nlemfuensis) was used as substrate to be fermented. Saccharomyces cerevisiae and LEVICA-25 reduced their population of methanogens. The populations at 4 h were of 268, 56.33, and 49.33 x 10-10 cfu mL-1 for the control, S. cerevisiae, and LEVICA-25, respectively. The methane production in the rumen at 24 h of fermentation was of 78.97, 45.21, and 21.52 ?L for the control treatment of star grass, S. cerevisiae, and LEVICA-25, respectively. S. cerevisiae increased in 1.75 times the population of cellulolytic bacteria, and LEVICA-25 multiplied by 2.25 the population of total viable bacteria. The number of protozoa was of 12.55, 16.30, and 17.55 x 10-5 cells mL-1 for the treatments A, B, and C, respectively. It was concluded that the preparations with Saccharomyces cerevisiae yeasts and LEVICA-25 reduced the methanogens and the ruminal methanogenesis, which provides the possibility of using them to enhance the efficiency in the use of the energy in ruminants. This could contribute to mitigate the impact of these gases on the environment. Key words: Saccharomyces cerevisiae, LEVICA-25, methnogens, rumen, methane, energy.